2018
DOI: 10.1080/23744235.2018.1453945
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of a multiplex serological test for the preoperative diagnosis of prosthetic joint infection: a prospective study

Abstract: Multiplex serological test performed well among patients with chronic staphylococcal prosthetic infection. This approach could contribute to PJI diagnosis especially in patients for whom the pre-operative analysis of joint fluid is not informative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
2
4
1
Order By: Relevance
“…The sensitivity and specificity of the detection of anti-staphylococcal antibodies in our study are close to those reported by Marmor et al (72.3% and 80.7%, respectively) and lower than those reported by De Seynes et al (87.5% and 93.5%, respectively) [9,10]. The specificity is notably lower than that reported by De Seynes et al with the high number of positive serological reactions among uninfected patients (18.1%) in our study.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The sensitivity and specificity of the detection of anti-staphylococcal antibodies in our study are close to those reported by Marmor et al (72.3% and 80.7%, respectively) and lower than those reported by De Seynes et al (87.5% and 93.5%, respectively) [9,10]. The specificity is notably lower than that reported by De Seynes et al with the high number of positive serological reactions among uninfected patients (18.1%) in our study.…”
Section: Discussionsupporting
confidence: 88%
“…Patients were distributed evenly between PJI and mechanical problems. All PJIs were chronic, with the presence of a sinus tract in a third of cases and a significantly increased CRP level, which reinforces the importance of measuring CRP in the diagnosis of PJI [7][8][9][10].…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations